Heat flux estimation for materials with pyrolysis and ablation. (1st March 2010) - Alestra, S.; Collinet, J.; Dubois, F.
In the development of future atmospheric re-entry vehicles, the heat shield (and its sizing) is one of the major challenges of the design. It is therefore important to know precisely aerothermal heat fluxes encountered during the re-entry, and the associated uncertainties. Identification of these stresses is possible only from indirect measurements, usually based on thermocouples located directly in the thermal protection. In this context, Astrium has developed since many years a one-dimensional tool to evaluate the heat loads on pyrolysable and ablative materials. An inverse problem is formulated to restore the heat flux encountered in re-entry problems, from temperature measurements made inside the material. We minimise the difference calculation/measurement with optimal control techniques (definition of a Lagrangian with adjoint and gradient techniques, with a quasi-Newton algorithm). On-ground and in-flight tests applications are presented, and first encouraging results using the automatic differentiation tool TAPENADE, developed at INRIA.